2022
DOI: 10.1186/s12893-022-01613-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of gastric schwannoma and review of related literature

Abstract: Background This study aimed to investigate the clinical features, diagnostic criteria, treatment options, and prognosis of patients with gastric schwannoma (GS). Methods We collected the clinical data of all patients pathologically diagnosed with GS in Zhejiang Provincial People's Hospital from May 2012 to October 2021. Results A total of 26 cases of GS were analyzed clinicopathologically, where the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
(25 reference statements)
0
16
1
Order By: Relevance
“…However, CD117 (usually positive in GIST) and SMA (usually positive in leiomyoma) were positive in 6.4% (5/78) and 17.9% (14/78) of the patients, respectively, suggesting that a single IHC parameter could not differentiate GISs from GIST and leiomyoma, and a combination of several parameters is necessary. Other studies also reported a positive expression of CD117 and SMA in GISs (20,22). No patient in the present study had c-KIT or PDGFRA mutation; therefore, we do not know the mutation status of c-KIT or PDGFRA in GISs.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…However, CD117 (usually positive in GIST) and SMA (usually positive in leiomyoma) were positive in 6.4% (5/78) and 17.9% (14/78) of the patients, respectively, suggesting that a single IHC parameter could not differentiate GISs from GIST and leiomyoma, and a combination of several parameters is necessary. Other studies also reported a positive expression of CD117 and SMA in GISs (20,22). No patient in the present study had c-KIT or PDGFRA mutation; therefore, we do not know the mutation status of c-KIT or PDGFRA in GISs.…”
Section: Discussioncontrasting
confidence: 70%
“…In the present study, the positive expression rate of S100 was 100%, and Dog-1 staining was negative in all the cases. We found that the expression of SOX-10 and Vimentin was positive in 97.2% (35/36) and 100% (32/32), respectively, which was rarely reported (22,(28)(29)(30), suggesting that these two markers may serve as important indicators for diagnosis of GISs (31). The Ki-67 index may help predict the malignancy of GISs; usually, Ki-67 > 10% is considered to be malignant (3).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Schwannomas that occur in the stomach are generally benign tumors. 14 Although there are individual case reports of concurrent gastric adenocarcinoma and gastric schwannoma, this event is rare, 15 , 16 and the extremely low incidence does not support a relationship between these tumors.…”
Section: Discussionmentioning
confidence: 99%